Synthesis and Characterization of Chitosan‐Based Polyelectrolyte Complexes Doped with Xanthene Dyes. Issue 18 (26th October 2015) - Slyusareva, Evgenia; Gerasimova, Marina; Slabko, Vitaliy; Abuzova, Nina; Plotnikov, Alexei; Eychmüller, Alexander
Abstract: Biocompatible chitosan‐based polyelectrolyte complexes (PECs) doped with xanthene dyes (fluorescein, eosin Y, erythrosin B, rhodamine 6G) were synthesized and characterized by scanning electron microscopy, dynamic light scattering, zeta potential measurements, and absorption and luminescence (including polarized, time‐resolved, and phosphorescence) spectroscopy. The results are discussed in terms of the mechanism and rigidity of dye–PEC binding, the heavy‐atom effect in dyes and PEC stability. Eosin Y is found to be the optimal dopant, providing both a high dye content in PECs and a high quantum yield of fluorescence. Abstract : Great PECs ! Biocompatible chitosan‐based polyelectrolyte complexes (PECs) doped with xanthene dyes were synthesized and characterized by scanning electron microscopy, dynamic light scattering, absorption, and luminescence spectroscopy. The results are discussed in terms of the mechanism of dye–PEC binding, the heavy‐atom effect in dyes, and PEC stability. Eosin Y is found to be the optimal dopant.